Introduction of Generative AI to Improve Digital Literacy of Sanggar Bimbingan AMI Penang Malaysia Children - Yusuf, Arief Rahman; Asmaroini, Ambiro Puji; Prasetyo, Angga; Wijaya, Etistika Yuni; Suhendar, Uki; Ramadhani, Desi Dwi; Sugiantoro, Erfan; Juppenny, Ryan (EQUATOR SINAR AKADEMIA, 2025)
Indonesian migrant workers' children (PMI) in Malaysia often face structural challenges in accessing formal education, thus relying on non-formal education services such as Sanggar Bimbingan (SB). SB AMI Penang, like most other SBs, operates with limited resources, which contributes to the digital literacy gap. However, digital literacy is a crucial competency for social and economic participation in the era of the Industrial Revolution 4.0. This international community service program aims to design and implement a Generative Artificial Intelligence (GenAI) introduction program as a pedagogical tool to improve the digital literacy competencies of children at SB AMI Penang. The community service methods include workshops and practical training. The results of structured and ethically oriented GenAI introduction activities proved effective in improving digital literacy in marginalized communities. The conclusion of this community service is that GenAI has the potential to be an equalizing tool to bridge the digital divide faced by Indonesian diaspora children.